PENGEMBANGAN MODUL IPA BERBASIS INQUIRY LESSON PADA MATERI USAHA DAN PESAWAT SEDERHANA UNTUK MENINGKATKAN KREATIVITAS ILMIAH SISWA - Siti Zulaichah; Sukarmin Sukarmin; Mohammad Masykuri (EDUSAINS, 2021)
THE DEVELOPMENT OF INQUIRY LESSON-BASED SCIENCE MODULE IN WORK AND SIMPLE MACHINE MATERIAL TO IMPROVE STUDENTS’ SCIENTIFIC CREATIVITY  AbstractThis research aimed to: 1) develop inquiry lesson-based science modules to improve student’s scientific creativity, 2) determine the feasibility of an inquiry lesson-based science module and 3) find out the effectiveness of inquiry lesson-based science modules to improve students’ scientific creativity. The science module material developed is work and simple machines. The module learning steps are arranged according to the inquiry lesson syntax and students’ scientific creativity indicators. The type of research is research and development (RnD) used Borg and Gall procedure that modified into 9 stages: 1) research and information collection, 2) planning, 3) initial product development, 4) initial field trial, 5) initial product revisions, 6) small-scale trial, 7) second product revisions, 8) operational field trial and 9) final product revisions. Characteristics of the module analyzed using descriptive analysis, module feasibility analyzed based on criteria scores and the module effectiveness analyzed using N-gain score. The result showed that: 1) inquiry lesson-based module has been successfully developed with characteristics according to the inquiry lesson models to improve students’ scientific creativity, 2) inquiry lesson-based module was very feasible used in learning process, 3) inquiry lesson-based module was effective in improving students’ scientific creativity with N-gain score of 0,55.AbstrakPenelitian ini bertujuan untuk: 1) mengembangkan modul IPA berbasis inquiry lesson untuk meningkatkan kreativitas ilmiah siswa, 2) mengetahui kelayakan modul IPA berbasis inquiry lesson, 3) mengetahui keefektifan modul IPA berbasis inquiry lesson untuk meningkatkan kreativitas ilmiah siswa. Modul yang dikembangkan yaitu materi Usaha dan Pesawat. Langkah-langkah pembelajaran pada modul disusun sesuai sintak inquiry lesson dan diintegrasikan dengan indikator kreativitas ilmiah siswa. Jenis penelitian yang digunakan yaitu penelitian dan pengembangan  (RnD) menggunakan model pengembangan Borg and Gall yang dimodifikasi menjadi 9 tahap meliputi: 1) penelitian pendahuluan dan pengumpulan informasi, 2) perencanaan, 3) pengembangan produk awal, 4) uji coba awal, 5) revisi produk awal, 6) uji coba terbatas, 7) revisi produk kedua, 8) uji coba lapangan operasional, 9) revisi produk akhir. Analisis data yang digunakan adalah analisis deskriptif untuk mendeskripsikan karakteristik modul, analisis kelayakan modul berdasarkan skor kriteria, analisis keefektifan modul untuk meningkatkan kreativitas ilmiah siswa berdasarkan skor N-gain. Hasil penelitian menunjukkan bahwa: 1) modul IPA pada materi usaha dan pesawat sederhana telah berhasil dikembangkan dengan karakteristik sesuai model inquiry lesson untuk meningkatkan kreativitas ilmiah siswa, 2) modul IPA berbasis inquiry lesson sangat layak digunakan dalam pembelajaran, 3) modul IPA berbasis inquiry lesson efektif meningkatkan kreativitas ilmiah siswa dengan skor N-gain sebesar 0,55.